Identification of a bipartite nuclear localization signal in the silkworm Masc protein. Issue 14 (21st June 2016) - Sugano, Yudai; Kokusho, Ryuhei; Ueda, Masamichi; Fujimoto, Masaru; Tsutsumi, Nobuhiro; Shimada, Toru; Kiuchi, Takashi; Katsuma, Susumu
Abstract : The silkworm Masculinizer ( Masc ) gene encodes a CCCH‐tandem zinc finger protein that controls both masculinization and dosage compensation. Masc protein is a nuclear protein, but the mechanism underlying the transport of this protein into the nucleus has not yet been elucidated. Here, we identified a functional bipartite nuclear localization signal (NLS) located between residues 274 and 290 of the Masc protein. Sequence comparison revealed that this bipartite NLS is evolutionarily conserved in Masc proteins from other lepidopteran insects. Furthermore, we showed that the degree of nuclear localization is not associated with the masculinizing activity of the Masc protein. Abstract :